Description of a second species in the enigmatic Southeast Asian genus Platygeniops (Coleoptera: Scarabaeidae: Cetoniinae) - Jákl, Stanislav; Krikken, Jan (Zootaxa, 2011)
A second species of Platygeniops Krikken, 1978 (Scarabaeidae: Cetoniinae: Trichiini: Osmodermatina) is described from the Myanmar-Thai-Malay isthmus and peninsula. The description of Platygeniops elongatus new species is based on two males and a female. The new species is compared with P. exspectans Krikken, 1978 from the Malay Peninsula and Borneo. The genus is re-diagnosed and its enigmatic status is briefly discussed.